Randomized comparative trial of three antivenoms in the treatment of envenoming by lance-headed vipers (Bothrops jararaca) in Sao Paulo, Brazil. - Cardoso, J; Fan, H; França, F; Jorge, M; Leite, R; Nishioka, SA; Avila, A; Sano-Martins, I; Tomy, S; Santoro, M (1993)
In São Paulo City, Brazil, 121 patients with moderately severe envenoming by Bothrops snakes (principally B. jararaca) were randomized for treatment with Brazilian polyspecific Bothrops antivenoms: Instituto Butantan (39 patients), Instituto Vital Brazil (41), Fundação Ezequiel Dias (FUNED) (41). The initial dose was four ampoules (40 ml) in 89 patients with less severe envenoming and eight ampoules (80 ml) in 32 patients with more severe envenoming. A second dose of four ampoules was required in 20 patients. Patients receiving the three antivenoms were comparable in all respects before treatment. There were no deaths. The majority showed rapid clinical improvement, resolution of local envenoming, cessation of bleeding and restoration of blood coagulability. No differences in the efficacy of the three antivenoms were revealed by clinical or laboratory observations, including measures of haematological, haemostatic and biochemical abnormalities. Twelve patients developed abscesses (Butantan 1, Vital Brazil 6, FUNED 5) and seven developed local necrosis (3,1,3). Of 88 patients followed up 20-30 days after the bite 33 (37.5%) still had symptoms or signs of local envenoming, especially swelling. Early (anaphylactic) reactions were unexpectedly frequent after all three antivenoms but were significantly more frequent with Butantan (87%) than with Vital Brazil (37%) or FUNED (56%) antivenoms (p < 0.001). A possible explanation was the higher total protein content and percentage immunoglobulin of Butantan antivenom. The doses of antivenom recommended in Brazil and used in this study may be unnecessarily high, resulting in an unacceptably high incidence of reactions. Results of the study should prompt a critical re-evaluation of antivenom production techniques and dosage recommendations in Brazil.